Designated survivor. The complete first season [videorecording (DVD)] - McGuigan, Paul, 1963-; Turner, Brad; Sutherland, Kiefer, 1966-; McElhone, Natascha, 1969-; Canto, Adan, 1981-; Ricci, Italia; Garrett, LaMonica (SDS, 2021)
Follows the adventures of a low-ranking cabinet member when he becomes President of the United States after the sitting president and other cabinet members are killed.